Comparison of the financial structures of manufacturing and commerce companies listed on the SGX. - Lee, Huimin. (2008)
This paper aims to explore the factor patterns of financial ratios and identify the representative financial ratios for each of the extracted factors for the two industries. A comparison will also be made to find out if there exist differences in the underlying financial structures of these two industries.